2021
DOI: 10.3390/healthcare9030353
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Public Spending on Health and Socio-Economic Development in the European Union: An Analysis from the Perspective of the Sustainable Development Goals

Abstract: In recent years, healthcare has become a fundamental pillar of the level of well-being of any society. With the aim of improving the lives of countries and societies, in 2015 the United Nations (UN) approved the 2030 Agenda for Sustainable Development. Among the Sustainable Development Goals (SDGs) set out in the Agenda are health and well-being (O3) and the reduction of inequalities (O10). The general objective of this paper is to analyse the impact that the level of socioeconomic development, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
1
3
0
3
Order By: Relevance
“…De acuerdo con el análisis de los resultados presentados, la tendencia de la inversión en salud tiene una ejecución presupuestal desigual y en la mayoría de las provincias su ejecución fue por debajo de los 13 millones de soles. Esto sugiere que existe desigualdad de oportunidades, lo que se relaciona con el estudio de Peña et al quien indica que en los países de la Unión Europea existe desigualdad a causa de diferencias territoriales y ello conlleva a reducir el acceso a servicios de salud y menores niveles de bienestar, por lo que no se descarta la inversión en salud puesto que reduce las desigualdades y a su vez un adecuado manejo de los recursos también ejerce un efecto positivo en el bienestar (Peña et al, 2021).…”
Section: Resultados Tendencia De La Ejecución Del Gasto Público De Ca...unclassified
See 2 more Smart Citations
“…De acuerdo con el análisis de los resultados presentados, la tendencia de la inversión en salud tiene una ejecución presupuestal desigual y en la mayoría de las provincias su ejecución fue por debajo de los 13 millones de soles. Esto sugiere que existe desigualdad de oportunidades, lo que se relaciona con el estudio de Peña et al quien indica que en los países de la Unión Europea existe desigualdad a causa de diferencias territoriales y ello conlleva a reducir el acceso a servicios de salud y menores niveles de bienestar, por lo que no se descarta la inversión en salud puesto que reduce las desigualdades y a su vez un adecuado manejo de los recursos también ejerce un efecto positivo en el bienestar (Peña et al, 2021).…”
Section: Resultados Tendencia De La Ejecución Del Gasto Público De Ca...unclassified
“…A pesar de existir discrepancias en la literatura académica sobre el papel de la inversión pública en salud en la reducción de la pobreza monetaria, los resultados hallados en este estudio corroboran la postura a favor de la relación IP-P/B. Esto quiere decir que los resultados obtenidos en el estudio son consistentes con las conclusiones a las que arribaron otros estudios que destacan la importancia de invertir en salud para mejorar el bienestar de las personas (Bernet et al, 2018;Oluwaseyi et al, 2022;Peña et al, 2021;Pinzón et al, 2014;Qin et al, 2021;Rodríguez et al, 2018).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In 2017, the Polish population totaled 37,975,000 people; GDP per capita at purchasing power parity was EUR 20,900; life expectancy at birth was 77.8 years, and health expenditure amounted to EUR 1,507 per person. In 2017, Poland allocated 6.5% of its GDP to health care [4,5]. The number of preventable deaths due to prevention by prophylaxis is 218/100 thousands and the number of preventable deaths thanks to medical intervention -130/100 thousands; the number of doctors per 1,000 inhabitants -2.3; the number of nurses -5.1 per 1,000 inhabitants [6], and the number of primary care physicians accounted for 9% of all physicians (Tab.…”
Section: Comparison Of Health Care Systems In Poland and Greatmentioning
confidence: 99%
“…The European Commission, in its report on inequalities in access to health care, concluded that inhabitants of countries with a lower socioeconomic level have significant difficulties in accessing health care [14], thus delaying diagnoses and enhancing the risk of hospitalization and readmission [15]. This situation increases the costs of health services [16]- [18] and leads to inequities. Consequently, better alignment of both competences and funding of primary care centers might reduce the need for unnecessary hospital admissions, prevent avoidable readmissions and limit inappropriate use of emergency care [19].…”
Section: Introductionmentioning
confidence: 99%